2001
DOI: 10.1152/jappl.2001.91.2.645
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac atrophy after bed rest and spaceflight

Abstract: Cardiac muscle adapts well to changes in loading conditions. For example, left ventricular (LV) hypertrophy may be induced physiologically (via exercise training) or pathologically (via hypertension or valvular heart disease). If hypertension is treated, LV hypertrophy regresses, suggesting a sensitivity to LV work. However, whether physical inactivity in nonathletic populations causes adaptive changes in LV mass or even frank atrophy is not clear. We exposed previously sedentary men to 6 (n = 5) and 12 (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
265
4
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(300 citation statements)
references
References 55 publications
17
265
4
6
Order By: Relevance
“…First, tissue Doppler imaging may be more sensitive than conventional echocardiography for detection of abnormalities in LV diastolic function in individuals with SCI. Second, our data showing lower Em and higher E/Em in subjects with SCI corroborate previous reports demonstrating impaired LV compliance in individuals subjected to prolonged bed rest and space flight, 7,8 thus indicating that physical inactivity may be associated with diastolic dysfunction. Nevertheless, this latter assumption is challenged by the lack of influence of injury level on LV diastolic function, as shown herein.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, tissue Doppler imaging may be more sensitive than conventional echocardiography for detection of abnormalities in LV diastolic function in individuals with SCI. Second, our data showing lower Em and higher E/Em in subjects with SCI corroborate previous reports demonstrating impaired LV compliance in individuals subjected to prolonged bed rest and space flight, 7,8 thus indicating that physical inactivity may be associated with diastolic dysfunction. Nevertheless, this latter assumption is challenged by the lack of influence of injury level on LV diastolic function, as shown herein.…”
Section: Discussionsupporting
confidence: 91%
“…6 Similarly, the development of LV diastolic dysfunction has been reported in individuals subjected to prolonged physical inactivity, 7,8 thereby suggesting that patients with SCI might be at a higher risk of developing abnormalities in LV function. The aim of this study was to investigate cardiac functional and structural parameters in SCI and able-bodied subjects and evaluate the impact of clinical, hemodynamic, metabolic and inflammatory variables in this regard.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, supine exercise in a LBNP chamber (58 ± 2 mmHg LBNP) has been reported to maintain aerobic fitness and sprint speed during 15 d of 6˚head-down bed rest (Watenpaugh et al, 2000). Thus, exercise combined with LBNP appears to provide an effective procedure to stress the cardiovascular system (Hargens, 1994), and may be useful in maintaining upright exercise capacity and prevent orthostatic intolerance during longer bed rest periods or space-flight (Watenpaugh et al, 2000;Perhonen et al, 2001;Schneider et al, 2002). LBNP has been combined with many exercise modalities, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Watenpaugh et al (2000) also reported that daily supine exercise in a LBNP chamber at 1.0-1.2 body weight (58 ± 2 mmHg LBNP) maintains aerobic fitness and sprint speed during 15 days of 6c head-down bed rest. Such preservation of submaximal responses after bed rest suggests that exercise combined with LBNP may be effective in maintaining upright exercise capacity during longer bed rest periods (Perhonen et al, 2001;Schneider et al, 2002). LBNP has been also used for preventing orthostatic intolerance and micogravity-induced cardiac remodeling/atrophy after space flight and for training astronauts (Watenpauch, 2001).…”
Section: Discussionmentioning
confidence: 99%